STRATEGI KOMUNIKASI PIMPINAN DALAM MENINGKATKAN KINERJA PEGAWAI DI LINGKUNGAN UNIVERSITAS BUANA PERJUANGAN KARAWANG - Meila Hasanah Amri (Jurnal Komunikasi, 2026)
Leadership communication plays a significant role in determining employee performance within organizational settings, including higher education institutions. As a growing university, Universitas Buana Perjuangan Karawang requires well structured communication strategies to ensure employees perform effectively and contribute to institutional objectives. This study aims to explore leadership communication strategies that can enhance employee performance at UBP Karawang. The research employs a literature review method by analyzing theories related to organizational communication, leadership, and human resource management. The results show that several communication approache such as two way communication, feedback mechanisms, transparent information sharing, persuasive communication, and the utilization of internal communication media positively influence employees’ motivation, discipline, and productivity. These findings emphasize that effective leadership communication is a crucial element in fostering a professional, supportive, and performance-driven work environment